Histopathologic Evaluation of Nonalcoholic Fatty Liver Disease in Hypothyroidism-Induced Rats - Şule Demir; Mustafa Ünübol; Serap Ünübol Aypak; Emrah İpek; Serdar Aktaş; Gamze Sevri Ekren; Murat Yılmaz; Recai Tunca; Engin Güney (International Journal of Endocrinology)
It is speculated that thyroid hormones may be involved in nonalcoholic fatty liver disease (NAFLD) pathogenesis. A literature scan, however, demonstrated conflicting results from studies investigating the relationship between hypothyroidism and NAFLD. Therefore, our study aims to evaluate NAFLD, from the histopathologic perspective, in hypothyroidism-induced rats. Wistar rats were divided into 2 groups: the experimental group consumed water containing methimazole 0.025% (MMI, Sigma, USA) for 12 weeks and the control group consumed tap water. At the end of week 12, serum glucose, ALT, AST, triglyceride, HDL, LDL, TSH, fT4, fT3, visfatin, and insulin assays were performed. Sections were stained with hematoxylin-eosin and “Oil Red-O” for histopathologic examination of the livers. In our study, we detected mild hepatosteatosis in all hypothyroidism-induced rats. There was statistically significant difference with respect to obesity between the two groups (p<0.001). The mean fasting blood glucose was 126.25 ± 23.4 mg/dL in hypothyroidism-induced group and 102.63 ± 15.51 mg/dL in the control group, with a statistically significant difference between the groups (p=0.032). The two groups did not differ statistically significantly with respect to visfatin levels (p>0.05). In conclusion, we found that hypothyroidism-induced rats had mild hepatosteatosis as opposed to the control group histopathologically. Our study indicates that hypothyroidism can cause NAFLD.